Organization resource planning systems and their impact on organizational creativity: The mediating role of organizational commitment (An applied study on banks operating in the Riyadh region of the Kingdom of Saudi Arabia - Assistant Prof. Dr. Munif Naif Alotaibi (مجلة الدراسات الاقتصادية والادارية)
This research addresses the role of organizational commitment as a mediating variable in enhancing the interactive relationship between organization resource planning systems and organizational creativity, an analytical research in banks operating in the Riyadh region in the Kingdom of Saudi Arabia. This research aimed to identify the impact of organization resource planning systems in all its dimensions on organizational creativity across banks operating in the Riyadh region, and to identify the impact of organization resource planning systems on organizational commitment across banks operating in the Riyadh region, and to identify the impact of organizational commitment on organizational creativity across banks. operating in the Riyadh region, and determining the extent to which the regulatory commitment of banks operating in the Riyadh region contributes as a mediating variable in the relationship between organization resource planning systems in its dimensions and organizational creativity. The researcher relied on the questionnaire list as a tool to collect the data necessary to test the research hypotheses. The population of this research included branches of Saudi banks in Riyadh Governorate (Al-Ahli Bank - Al-Bilad Bank - Al-Rajhi Bank - Alinma Bank). It is represented by branch managers and department heads from senior, middle and executive management, where a random sample of (158) individuals was selected. The research found that there is a positive statistical significant effect of the dimensions of organization resource planning systems on organizational creativity through application in banks operating in the Riyadh region, and there is a positive statistical significant effect of the dimensions of organization resource planning systems on organizational commitment to application in banks operating in the Riyadh region, and there is a statistically significant effect Organizational commitment has a positive effect on organizational creativity in application in banks operating in the Riyadh region. Organizational commitment also mediates the relationship between the dimensions of organization resource planning systems and organizational creativity in application in banks operating in the Riyadh region.